2016
DOI: 10.1016/j.encep.2016.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Validation de la version française de la Binge Eating Scale : étude de sa structure factorielle, de sa consistance interne et de sa validité de construit en population clinique et non clinique

Abstract: In this study, we validated a psychometrically sound French version of the Binge Eating Scale, both in a non-clinical and a clinical sample. The psychometric properties of the French version of the BES are comparable to its original version with a one-factor structure. The BES is a useful tool to assess binge eating disorder in obese patients (e.g., bariatric surgery candidates), but might not differentiate between binge eating disorder and bulimia nervosa in underweight and optimal weight subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 23 publications
4
28
0
3
Order By: Relevance
“…While the BES is best utilized as a screening tool and a positive screen is not necessarily equivalent to a diagnosis of BED, looking only at positive screens for BES, a study using the BES in an obese outpatient population found that 14.6% of men and 10.6% of women screened positive for BED [ 25 ]. Another cross-sectional study utilizing the BES in patients undergoing evaluation for bariatric surgery found that 17% of patients screened positive [ 20 ]. In both studies, the percentage of people who screened positive was well below our 23.1%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the BES is best utilized as a screening tool and a positive screen is not necessarily equivalent to a diagnosis of BED, looking only at positive screens for BES, a study using the BES in an obese outpatient population found that 14.6% of men and 10.6% of women screened positive for BED [ 25 ]. Another cross-sectional study utilizing the BES in patients undergoing evaluation for bariatric surgery found that 17% of patients screened positive [ 20 ]. In both studies, the percentage of people who screened positive was well below our 23.1%.…”
Section: Discussionmentioning
confidence: 99%
“…The BES has been shown to have good internal consistency and validity in studies and across several languages [ 20 - 23 ]. The BES has also been frequently used to assess for BED in patients seeking bariatric surgery [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…We considered binge eating as a categorical variable (significant binge eating if BES score ≥18). We used the validated French version [ 24 ]. The Cronbach’s alpha for the current study was 0.83.…”
Section: Methodsmentioning
confidence: 99%
“…Gormally et al (1982) originally proposed a two-factor structure, dividing the items into cognitive and behavioral BE. Since then, the scale has been validated in French, Portuguese, English, Italian, Malay, and Spanish (Mexican) (Gormally et al, 1982; Ricca et al, 2000; Freitas et al, 2006; Zúñiga and Robles, 2006; Robert et al, 2013; Duarte et al, 2015; Brunault et al, 2016). Of these studies, only four have studied the factorial structure of the BES, with differing results.…”
Section: Introductionmentioning
confidence: 99%
“…However, when the authors studied the sensitivity, specificity, and reliability of the BES, they found a unidimensional structure. More recently, Duarte et al (2015) and Brunault et al (2016) provided evidence of a one-factor structure in a sample of Portuguese women from the general population and in French non-clinical and clinical populations, respectively. Using CFA, Duarte et al (2015) found a good fit for a one-factor structure of the BES, with appropriate reliability estimates for both the scale and the items, and good convergent validity.…”
Section: Introductionmentioning
confidence: 99%